Physical activity and cold pain tolerance in the general population - Årnes, Anders; Nielsen, Christopher Sivert; Stubhaug, Audun; Fjeld, Mats Kirkeby; Hopstock, Laila Arnesdatter; Horsch, Alexander; Johansen, Aslak; Morseth, Bente; Wilsgaard, Tom; Steingrímsdóttir, Ólöf Anna (European Journal of Pain, 2020)
This is the peer reviewed version of the following article: Årnes, A.P., Nielsen, C.S., Stubhaug, A., Fjeld, M.K., Hopstock, L.A., Horsch, A., . Steingrímsdóttir, O.A. (2020). Physical activity and cold pain tolerance in the general population. European Journal of Pain, 25 , 637– 650, which has been published in final form at https://doi.org/10.1002/ejp.1699 . This article may be used for non-commercial purposes in accordance with Wiley Terms and Conditions for Use of Self-Archived Versions. Background - The relationship between habitual physical activity (PA) and experimental pain tolerance has been investigated in small samples of young, healthy and/or single‐sex volunteers. We used a large, population‐based sample to assess this relationship in men and women with and without chronic pain. Methods - We used data from the sixth and seventh Tromsø Study surveys (2007–2008; 2015–2016), with assessed pain tolerance of participants with the cold pressor test (CPT: dominant hand in circulating cold water at 3°C, maximum test time 106 s), and self‐reported total amount of habitual PA in leisure time (n = 19,087), exercise frequency (n = 19,388), exercise intensity (n = 18,393) and exercise duration (n = 18,343). A sub‐sample had PA measured by accelerometers (n = 4,922). We used Cox regression to compare CPT tolerance times between self‐reported PA levels. For accelerometer‐measured PA, we estimated hazard ratios for average daily activity counts, and for average daily minutes of moderate‐to‐vigorous PA done in bouts lasting 10 min or more. Models were tested for PA‐sex, and PA‐chronic pain and PA‐moderate‐to‐severe chronic pain interactions. Results - Leisure‐time PA, exercise intensity and exercise duration were positively associated with CPT tolerance (p < .001; p = .011; p < .001). More PA was associated with higher CPT tolerance. At high levels of leisure‐time PA and exercise intensity, men had a significantly higher CPT tolerance than women. Accelerometer‐measured PA was not associated with CPT ...